2021
DOI: 10.1103/physrevb.103.184101
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the superconducting high-pressure phase of Sc3CoC4

Abstract: We investigate pressure-induced structural changes to the Peierls-type distorted low-temperature phase of the low-dimensional Sc 3 CoC 4 as a possible origin of its pressure-enhanced superconductivity. By means of cryogenic high-pressure x-ray diffraction experiments we could reveal subtle, but significant structural differences between the low-temperature phase at ambient and elevated pressures. We could thus establish the structure of the superconducting phase of the title compound, which interestingly still… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(25 citation statements)
references
References 85 publications
3
22
0
Order By: Relevance
“…It has been shown that the complex carbide Sc 3 CoC 4 becomes a volume superconductor at a transition temperature T c of 4.5 K under only modest hydrostatic pressures (p ! 0.5 GPa) (Wang et al, 2016;Langmann et al, 2021). At the Eickerling et al, 2013;Langmann et al, 2021).…”
Section: Measurements Under Lt/hp Conditionsmentioning
confidence: 96%
See 4 more Smart Citations
“…It has been shown that the complex carbide Sc 3 CoC 4 becomes a volume superconductor at a transition temperature T c of 4.5 K under only modest hydrostatic pressures (p ! 0.5 GPa) (Wang et al, 2016;Langmann et al, 2021). At the Eickerling et al, 2013;Langmann et al, 2021).…”
Section: Measurements Under Lt/hp Conditionsmentioning
confidence: 96%
“…0.5 GPa) (Wang et al, 2016;Langmann et al, 2021). At the Eickerling et al, 2013;Langmann et al, 2021). Yet, previously published structural data were collected at $4 GPa and 37 K and therefore still above the T c of the compound (Langmann et al, 2021).…”
Section: Measurements Under Lt/hp Conditionsmentioning
confidence: 99%
See 3 more Smart Citations